Gestión de talento humano y rendimiento laboral - Cabezas Ramos, Carlos Bolívar (2022)
This research emphasizes on human talent management and work performance, mainly focused on a service station dedicated to retail fuel sales. The main objective of this research is to identify the effect that human talent management has on labor performance and for this purpose a mixed approach research of inductive purpose, direct observation, surveys and interviews were required in a population of 25 workers; the results show that the customer service process has 39% of sub-processes developed by the dispatchers; of which 17% have an opportunity for improvement, while 44% are not fully complied with………..